Statistical methods applied in pharmacotherapy - Marković Srđan Z.; Vuković Mira H.; Kocev Nikola I.; Kastratović Dragana A.; Vukmirović Srđan N. (Srpsko lekarsko drustvo, 2019)
Introduction: Pharmacotherapy dealing with drug research is extremely complex process because in addition to basic knowledge in pharmacology, it includes both knowledge in clinical medicine and medical statistics. Methods: Statistical methods applied in medical research have been studied on examples of individual statistical methods applied in particular clinical trials. Topic: the following problems have been discussed: study design, study plan, criteria for selecting patients, the required and sufficient minimum number of patients in the clinical trial, the selection of the most commonly used descriptive and analytical statistical procedures, but also a critical review of analytical statistical procedures that have great potential in checking the conformity of everyday clinical practice with evidence-based medicine. Conclusions: Knowledge of statistical methods is a valuable companion and tool of clinicians, since it enables them to carry out appropriate research with the best possible conclusions based on medical evidence.